Execution of smart electric vehicle charging station driven by RE technology using soft computing approach - K, Vinoth Kumar; Sujitha, S; Stalin, B; Buvana, D; Josh, F T; Vinodha, K; Ramya, K C; Saravanakumar, R; Logeswaran, D (2021 Innovations in Power and Advanced Computing Technologies (i-PACT), 2021)
This paper outlines potential demand for electric vehicles, charging station infrastructure and its challenges for the India scenario, as well as the increasing liberalization and expansion of production, transmission and distribution. Distributed and renewable electricity generation and distribution, as well as market processes related to energy allocation and energy mix. is the subject of evolutionary development with improved performance and reliability. Structural analysis of respective parameters was performed for the commercial scope of electric vehicles in the existing energy market and regulatory concerns are taken into account to describe a scenario in which a company global control of electric vehicle charging and service provision of ancillary networks. Experimental results show confirmatory results.